2007
DOI: 10.1161/circulationaha.106.645416
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of Calcium-Dependent Tyrosine Kinase PYK2 in Endothelial Nitric Oxide Synthase–Mediated Angiogenic Response and Vascular Function

Abstract: Background-The involvement of Ca 2ϩ -dependent tyrosine kinase PYK2 in the Akt/endothelial NO synthase pathway remains to be determined. Methods and Results-Blood flow recovery and neovessel formation after hind-limb ischemia were impaired in PYK2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 39 publications
1
48
1
Order By: Relevance
“…Generation of Pyk2-knockout mice allowed a better understanding of the role of this kinase in many physiologic context, including macrophage migration and osteoclast activation. 27,38,39 In the present study, we report that Pyk2-deficient platelets show a defective activation of PI3K␤ after integrin ␣2␤1-mediated adhesion. A possible role for Pyk2 in the regulation of platelet PI3K activity has been hypothesized previously on the basis of some circumstantial evidence.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Generation of Pyk2-knockout mice allowed a better understanding of the role of this kinase in many physiologic context, including macrophage migration and osteoclast activation. 27,38,39 In the present study, we report that Pyk2-deficient platelets show a defective activation of PI3K␤ after integrin ␣2␤1-mediated adhesion. A possible role for Pyk2 in the regulation of platelet PI3K activity has been hypothesized previously on the basis of some circumstantial evidence.…”
supporting
confidence: 51%
“…Generation and characterization of PI3K␤ KD , PI3K␥ KD , and Pyk2-knockout mice was described previously. [25][26][27] The use of mice for our experimental work was approved by the Ethics Committee of the University of Pavia. The rabbit polyclonal Abs against Rap1 (121), against Pyk2 (N-19), as well as the mAb anti-tubulin (DM1A) were from Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies (15,18) have reported that Pyk2 is activated by vagal stimulation through the ACh receptor. We explored this phenomenon in the whole heart to probe its possible role in arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…Pyk2 is expressed in cardiomyocytes, cardiac fibroblasts, vascular smooth muscle cells, and vascular endothelial cells (3,8,18,22,27). Pyk2 signaling has been implicated in the induction of pressure overload-induced left ventricular (LV) hypertrophy and the transition to heart failure (4).…”
mentioning
confidence: 99%
“…19 Moreover, endothelial cell migration and tube formation promoted by VEGF was found to be strongly impaired in the absence of Pyk2. 20 A recent study also showed that Pyk2 is implicated in reactive oxygen species generation and reactive oxygen speciesmediated proinflammatory events involved in atherosclerosis. 21 These previous observations clearly point to a relevant role for Pyk2 in the cardiovascular system.…”
Section: Introductionmentioning
confidence: 98%